Behavioural changes in patients with intellectual disability treated with perampanel - Andres, E.; Kerling, Frank; Hamer, Hajo; Kasper, Burkhard; Winterholler, Martin (Acta Neurologica Scandinavica, 2017)
The aim of this cross-sectional retrospective study was to assess the tolerability and efficacy of perampanel in patients with drug-resistant epilepsy who also suffered from intellectual disability (ID).We used an industry-independent, non-interventional retrospective evaluation based on standardized, daily seizure records. Twenty-seven patients with ID and drug-resistant epilepsy were started on perampanel between September 2012 and November 2015 after a 3-month observation period without perampanel treatment. Perampanel was given at a maximum dosage of 4-12 mg daily. Evaluation was carried out after 6, 12 and 24 months, including calculation of the retention rate. Mean seizure frequency was compared between the 3-month baseline period and subsequent 3-month treatment periods. The Clinical Global Impression scale was applied to assess qualitative changes in seizure severity, and the Aggressive Behaviour Scale (ABS) gave further insights into challenging behaviour.Perampanel was efficacious and well tolerated in five of 25 patients. In 18 patients, perampanel treatment was stopped, mainly because of adverse events (n=6), lack of efficacy (n=3) or both (n=9). Behavioural changes were documented in 15 of 27 patients, with aggressive behaviour being the commonest effect; we observed ataxia (n=6) and sedation (n=8) in further patients. The ABS showed worsening of aggressive behaviour in six patients.Perampanel was well tolerated and efficacious in one-fifth of our patients. We observed challenging behaviour, ataxia and sedation in a relevant number of patients with ID under perampanel treatment. Further studies are warranted to explore the tolerability of perampanel in patients with ID.
EVALuna2:22550